How Does Foreign Direct Investment affect the Export Decisions of Firms in Ghana? - Abor, J.; Adjasi, C.K.D.; Hayford, M. (My University, 2008)
Foreign direct investment (FDI) has been identified to promote exports of host countries by augmenting domestic capital for exports, helping to transfer technology and new products for exports, facilitating access to new and large foreign markets, providing training for the local workforce, and upgrading technical and management skills. However, little is known on the role of FDI in the export behaviour of firms in developing countries. The main questions raised in this study are: how does FDI affect the export decisions of firms? How does FDI affect export performance of firms? This study examined the export-decision and export performance within the Ghanaian manufacturing sector on a panel of plants from 1991 to 2002. Using a probit model, the results show that FDI has a positive effect on firms' decision to export. The random effect results also reveal a positive relationship between FDI and export performance. Clearly, the results of this study indicate that FDI is very relevant in influencing the export decisions and export performance of Ghanaian firms. The findings have significant implications for policy in terms of promoting initiatives to encourage more FDI inflows in the country.